2001
DOI: 10.1097/00001756-200108080-00046
|View full text |Cite
|
Sign up to set email alerts
|

Imagining rotation by endogenous versus exogenous forces: Distinct neural mechanisms

Abstract: Previous neuroimaging studies of mental image transformations have sometimes implicated motor processes and sometimes not. In this study, prior to neuroimaging the subjects either viewed an electric motor rotating an angular object, or they rotated the object manually. Following this, they performed the identical mental rotation task in which they compared members of pairs of such figures, but were asked to imagine the figures rotating as they had just seen the model rotate. When results from the two rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
160
2
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(183 citation statements)
references
References 15 publications
18
160
2
3
Order By: Relevance
“…Evidence for an association between motor control and mental rotation stems both from functional imaging (Kosslyn et al 2001;Vingerhoets et al 2001) and behavioral studies (Funk et al 2005;Olivier et al 2004;Wexler et al 1998;Wiedenbauer and Jansen in press;Wiedenbauer et al 2007;Wohlschläger 2001;Wohlschläger and Wohlschläger 1998,). In the fMRI study by Kosslyn et al (2001), subjects first viewed an electric motor rotating an angular object or they rotated the object manually.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for an association between motor control and mental rotation stems both from functional imaging (Kosslyn et al 2001;Vingerhoets et al 2001) and behavioral studies (Funk et al 2005;Olivier et al 2004;Wexler et al 1998;Wiedenbauer and Jansen in press;Wiedenbauer et al 2007;Wohlschläger 2001;Wohlschläger and Wohlschläger 1998,). In the fMRI study by Kosslyn et al (2001), subjects first viewed an electric motor rotating an angular object or they rotated the object manually.…”
Section: Introductionmentioning
confidence: 99%
“…In the fMRI study by Kosslyn et al (2001), subjects first viewed an electric motor rotating an angular object or they rotated the object manually. Then they were asked to imagine the objects rotating as they had just seen the model rotate.…”
Section: Introductionmentioning
confidence: 99%
“…Memory is thought to be represented by changes in the same neural systems that perceive, analyze, and process sensory information (Squire 1986;Thompson 1986;Squire and ZolaMorgan, 1991;Zola-Morgan and Squire, 1993;Kosslyn et al, 1995;Gilbert 1998;Kosslyn et al, 2001;Super et al, 2001). In working memory, sensory information is temporarily stored, manipulated, and maintained in the neural system for later action (Baddeley 1992;Smith and Jonides, 1999;Fuster 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Turnbull et al (1997) report that people with lesions in ventrodorsal cortex have problems in recognizing objects that seem to require transformations of imagery, such as recognizing an object seen from an unusual perspective. And Kosslyn et al (2001) report the results of a brain imaging study in which subjects watched an object being rotated either by hand or by a machine, before undertaking a mental-rotation task involving a similar sort of object. They found that primary motor cortex was active only in the first ('by hand') condition; but that pre-motor cortex was activated in both conditions − suggesting that motor-schema planning of some sort lies at the bottom of all imagery transformation.…”
mentioning
confidence: 99%
“…There are good reasons to think that perceptual and quasi-perceptual (imagistic) states are globally broadcast to a wide range of inferential systems for forming memories, for creating new beliefs and emotions, and for practical reasoning (Baars, 1988(Baars, , 1997(Baars, , 2002(Baars, , 2003Dehaene et al, , 2003Baars et al, 2003;Kreiman et al, 2003). And there is good reason to think that motor-schemata can be used to create and transform such visual images (Kosslyn, 1994;Turnbull et al, 1997;Ganis et al, 2000;Richter et al, 2000;Kosslyn et al, 2001;Lamm et al, 2001). And there are also good reasons, I claim, for thinking that a limited capacity to reason with suppositions in the form of mental rehearsals of potential actions might have long pre-dated the evolution of human beings.…”
mentioning
confidence: 99%